Honey Analysis New Advances and Challenges - de Alencar Arnaut de Toledo, Vagner; Dechechi Chambó, Emerson (IntechOpen, 2020)
Honey Analysis - New Advances and Challenges discusses advances in honey research. Topics include the physicochemical characteristics of honey from stingless bees, the therapeutic properties of honey, melissopalynological analysis as an indicator of the botanical and geographical origin of honey, and methods for authenticating honey. Written by experts in the field, this book provides readers with an indispensable source of information, assisting them in future investigations of honey and beekeeping.